Integral Stability in Terms of Two Measures for Nonlinear Differential Systems with “Maxima” - Peiguang Wang; Qing Xu; Xiaojing Liu (Abstract and Applied Analysis)
This paper investigates relatively integral stability in terms of two measures for two differential systems with “maxima” by employing Lyapunov functions, Razumikhin method, and comparison principle. An example is given to illustrate our result.